Holmium Laser for Endoscopic Treatment of Benign Tracheal Stenosis - Verret,D. J. (2018)
Abstract Introduction Laryngotracheal stenosis is a difficult problem with varied etiology and various treatment options. The holmium laser represents another tool for the treatment of benign tracheal stenosis. Objectives To determine the utility of holmium laser treatment for benign tracheal stenosis with regards to safety and efficacy. Methods This was a retrospective case study examining patients with benign tracheal stenosis from 1998-2016 who underwent holmium laser treatment. Determining the safety of this procedure was the primary goal, and complications were monitored as a surrogate of safety. Results A total of 123 patients who underwent holmium laser treatment for benign tracheal stenosis were identified. In total, 123 patients underwent 476 procedures, with follow-up ranging from 1 month to 14 years. No intraoperative or post-operative complications were identified as a direct result of the use of this particular laser. Conclusions The holmium laser is an effective and safe laser to use for tracheal stenosis treatment. It is a contact laser with a short acting distance, which reduces the risk of injury to distal airway structures. Given the favorable experience reported here, the holmium laser should be considered when tracheal surgery is attempted.